Synthesis of silver nanoparticles by aqueous extract of Zingiber officinale and their antibacterial activities against selected species - Hussain Zawar; Jahangeer Muhammad; Rahman Shafiq ur; Ihsan Tamanna; Sarwar Abid; Ullah Najeeb; Aziz Tariq; Alharbi Metab; Alshammari Abdulrahman; Alasmari Abdullah F. (Polish Journal of Chemical Technology, 2023)
Silver nanoparticles have special plasmonic and antibacterial characteristics that make them efficient in a variety of commercial medical applications. According to recent research, chemically synthesized silver nanoparticles are harmful even in low concentrations. It was crucial to identify appropriate synthesis methods that may have low costs and be nontoxic to the environment. Zingiber officinale (ginger) extracts used to prepare silver nanoparticles were inexpensive and environmentally friendly, and the best physicochemical characteristics were analyzed. Silver nanoparticles were characterized by using UV-visible spectroscopy, Scanning electron microscopy (SEM), and X-ray diffraction (XRD). The surface Plasmon resonance peak at 425 nm was observed using UV-Visible spectroscopy. Scanning electron microscopy observed that the nanoparticles were spherical and ranged in size from 5 to 35 nm. The XRD pattern values of 2θ: 38.2o, 46.3o, and 64.58o are used to determine the planes (111), (200), and (220). The silver nanoparticle’s existence was verified by the face-centered cubic (FCC). Silver nanoparticles were found to have antibacterial efficacy against gram-positive Staphylococcus and gram-negative bacteria such as Pseudomonas aeruginosa, Klebsiella Aerogenes, Salmonella, Staphylococcus and Escherichia coli. The antibacterial activity of silver nanoparticles was observed using the agar well diffusion (AWD) method at three different concentrations (100 μg/ml, 75 μg/ml, and 50 μg/ml). The zone of inhibition measured against the bacterial strains pseudomonas Aeruginosa, Klebsiella aerogenes, Escherichia coli, Salmonella and Staphylococcus which were (18.4±1.25 mm, 16.9±0.74 mm, 14.8±1.25 mm), (16.8±0.96 mm, 14.6±0.76 mm, 14.0±1.15 mm), (19.7±0.76 mm, 18.2±0.66 mm, 15.4±1.15 mm), (16.6±0.67 mm, 14.2±0.23 mm, 12.8±0.78 mm) and (12±0.68 mm, 10±0.20 mm, 08±0.15 mm). These nanoparticles’ potent antibacterial properties may enable them to be employed as nanomedicines for a variety of gram-negative bacterial illness treatments.